What do homeopathic doctors think of vaccines? An international online survey. Issue 2 (May 2016) - Eizayaga, José Enrique; Waisse, Silvia
Abstract : Background and objectives: Parental refusal to vaccinate is a cause of serious concern. Use of homeopathy is believed to be a relevant reason for parents to refuse to vaccinate. However, vaccination is one of the main gaps dividing between medically qualified or not homeopathic practitioners. The present study sought to investigate the attitude of homeopathic doctors towards vaccination and associated variables. Methods: An international online survey was conducted with homeopathic doctors by means of an anonymous self-reported questionnaire in Portuguese or Spanish. Questions investigated sociodemographic and professional characteristics, overall opinion on vaccination and on some specific vaccines. Results: A total of 512 responses were obtained, 77.5% of respondents were from Latin American countries, 16.8% from Spain, with small numbers from several other countries. About 75.6% of the respondents considered vaccination safe, effective and necessary, while 12.5% stated they would not recommend vaccination under any circumstance. The variables significantly correlated with positive attitude towards vaccination were: working in the public health system (p = 0.04) and homeopathy not the main medical activity (p = 0.005). Homeopaths from Brazil, where homeopathy is officially accredited, were more favorable to vaccination compared to respondents from countries where homeopathy has inferior status (p < 0.001). Conclusion: The results show that there is no contradiction between homeopathy and primary prevention by means of vaccination. Highlights: Parental refusal to vaccinate is currently a cause of serious concern. Homeopathy is believed to be a relevant reason for refusal to vaccinate. An international online survey in Spanish and Portuguese was conducted with medically qualified homeopaths on their attitude toward vaccination. Most respondents consider vaccination effective and safe and recommend it to patients.